The Competition (Amendment) Bill 2007: a review and critique - Ghosh, Subhadip; Ross, Thomas W. (2009)
With the passage of the competition (Amendment) Bill (2007) India is poised to usher in a new era in competition policy, supported by sophisticated legislation that in many ways represents international best practices. However, there are uncertainities and challenges ahead as well. This article summarises the major features of the new law and critically examines its strength and weaknesses. concerns are expressed on how courts will interpret the primary objective of the legislation, and the degree to which the enforcement agency will be sufficiently funded and properly independent. - Reproduced.
Keywords: Competition